Do Wages Lead Inflation? Swiss Evidence - Attilio Zanetti (Swiss Journal of Economics and Statistics, 2007)
We construct a quarterly time series for nominal hourly wages and unit labour costs from 1975 onwards and investigate the empirical link between wages and CPI inflation in order to identify causality effects and assess the relevance of wages as an indicator for short-run price changes. We find evidence that prices systematically influence wages whereas the influence of wages on prices is much more sensitive to the choice of the sample period. In particular, the explanatory power of wages disappears in a low inflation environment. These findings move in the same direction as most evidence obtained with US data.
Keywords: E30; J30; 330; inflation; wages; unit labor costs; Granger causality